Genetic polymorphisms of PKLR gene and their associations with milk production traits in Chinese Holstein cows - Du, Aixia; Zhao, Fengru; Liu, Yanan; Xu, Lingna; Chen, Kewei; Sun, Dongxiao; Han, Bo (Frontiers in Genetics, 2022)
Our previous work had confirmed that pyruvate kinase L/R (PKLR) gene was expressed differently in different lactation periods of dairy cattle, and participated in lipid metabolism through insulin, PI3K-Akt, MAPK, AMPK, mTOR and PPAR signaling pathways, suggesting that PKLR is a candidate gene to affect milk production traits in dairy cattle. Here, we verified whether this gene has significant genetic associations with milk yield and composition traits in a Chinese Holstein cow population. In total, we identified 21 single nucleotide polymorphisms (SNPs) by resequencing the entire coding region and partial flanking region of PKLR gene, in which, two SNPs were located in 5' promoter region, two in 5' untranslated region (UTR), three in introns, five in exons, six in 3' UTR and three in 3' flanking region. The single marker association analysis displayed that all SNPs were significantly associated with milk yield, fat and protein yields or protein percentage (P ＜ 0.0497). The haplotype block containing all the SNPs, predicted by Haploview, had a significant association with fat yield and protein percentage (P < 0.0145). Further, four SNPs in 5' regulatory region and eight SNPs in UTR and exon regions were predicted to change the transcription factor binding sites and mRNA secondary structure, respectively, thus affecting the expression of PKLR, leading to changes in milk production phenotypes, suggesting that these SNPs may be the potential functional mutations for milk production traits in dairy cattle. In conclusion, we demonstrated that PKLR had significant genetic effects on milk production traits, and SNPs with significant genetic effects could be used as candidate genetic markers for genomic selection in dairy cattle.